Poly(4‐vinylphenol)/tetra‐n‐butylammonium iodide: Efficient organocatalytic system for synthesis of cyclic carbonates from CO2 and epoxides. Issue 33 (21st April 2017) - Wang, Xiangyong; Zhao, Yingying; Kodama, Koichi; Hirose, Takuji
ABSTRACT: An efficient polymer‐based catalytic system of poly(4‐vinylphenol) and tetra‐ n ‐butylammonium iodide was developed for the synthesis of cyclic carbonates from epoxides and CO2 . Owing to the synergistic effects of hydroxyl groups and iodide anions, this commercially available and metal‐free system was highly active for the reaction of various terminal epoxides under environmentally benign conditions, at 25 to 60 °C and atmospheric pressure of CO2, without the use of any organic solvents. The catalyst system can be easily separated by adding ether, and its ability was recovered by treating it with 40% CH3 CO2 H aq. The recyclability was investigated in detail for three substrates, epichlorohydrin, 1, 2‐epoxyhexane, and styrene oxide, using 1 H nuclear magnetic resonance analysis. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45189. Abstract :